Respuesta :
[tex]\bf \qquad \qquad \textit{compound proportional variation} \\\\ \begin{array}{llll} \textit{\underline{y} varies directly with \underline{x}}\\ \textit{and inversely with \underline{z}} \end{array}\implies y=\cfrac{kx}{z}\impliedby \begin{array}{llll} k=constant\ of\\ \qquad variation \end{array} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ \stackrel{\textit{\underline{y} varies jointly as \underline{a} and \underline{b} and inversely as }\sqrt{c}}{y=\cfrac{kab}{\sqrt{c}}}[/tex]
[tex]\bf \textit{we also know that } \begin{cases} y=96\\ a=8\\ b=6\\ c=16 \end{cases}\implies 96=\cfrac{k(8)(6)}{\sqrt{16}}\implies 96=\cfrac{48k}{4} \\\\\\ \cfrac{96\cdot 4}{48}\implies 8=k\qquad therefore\qquad \boxed{y=\cfrac{8ab}{\sqrt{c}}} \\\\\\ \textit{when } \begin{cases} a=7\\ b=5\\ c=25 \end{cases}\textit{ what is \underline{y}?}\implies y=\cfrac{8(7)(5)}{\sqrt{25}}\implies y=\cfrac{8(7)(5)}{5}\implies y=56[/tex]
y = 56
The initial statement is y varies as [tex]\frac{ab}{\sqrt{c} }[/tex]
To convert to an equation multiply by k the constant of variation
y = [tex]\frac{kab}{\sqrt{c} }[/tex]
y = 96 when a = 8 , b = 6 , c = 16
y = [tex]\frac{kab}{\sqrt{c} }[/tex]
hence k = [tex]\frac{y\sqrt{c} }{ab}[/tex]
= [tex]\frac{96\sqrt{16} }{8 x 6}[/tex] = [tex]\frac{96 x 4}{8 x 6}[/tex] = 8
Thus y = [tex]\frac{8ab}{\sqrt{c} }[/tex]
given a = 7 , b = 5 , c = 25 then
y = [tex]\frac{8 x 7 x 5}{\sqrt{25} }[/tex] = 8 × 7 = 56